Agricultura familiar integrada ao mercado: mediação política e transformações socioespaciais no assentamento rural Vale do Lírio/RN - França, Rosana Silva de (2005)
It s an application about the development of the family agriculture integrated to the market in which is detected the development of the relation of partnership between settled of agrarian reform and the capitalist enterprise. It s shown initially, a conceptual discussion about family agriculture, watching the historical contexts that characterize the expropriation and subordination of the category. This way, the family agriculture is contextual zed in the moment of the modernization of the agriculture, he rising of the social tension in the area of the restructuration of production and the globalization. Finding to understand the agrarian question in Rio Grande do Norte, it s characterized the acting of the state in promoting agrarian reform politics and redistribution of lands. This way, the research demonstrate the reality of the settled of Vale do Lírio, with the partnership of the Caliman Company S. A. in this context, it s emphasized the social geographic transformation in the settler. This way it was realized the analysis of the survey of data in a lot of public department, and the research of the area with use of application form, in 90% percent of the researched group, with interviewing with the leaders of this group and with the manager of the Company. The research demonstrates an analysis of the reality lived by this group, in the perspective the interests of the government and the capital.